Incidence of temperature and heat generation scenario on kaolinite mechanical behaviour (2017)
Kaolinite, as a clay material, exhibits variability of its properties in presence of temperature changes. This paper presents the results of an experimental study of thermal effects on the mechanical behaviour of kaolinite, as well, as the heat generation scenario. In the Homogeneous Heat Generation scenario (HHG), samples were subjected to a temperature treatment in a furnace at different temperatures, and Atterberg limits and unconfined compression tests were performed afterwards. In the Punctual Heat Generation scenario (PHG), an electric resistance heating element was used to heat the samples at different time lapses. Temperature profile inside the samples were gathered, and a CPT was performed. In the HHG scenario, Atterberg limits presented no change with temperature, but the undrained shar strength increased (Cu). In the PHG scenario, temperature and Cu presented a remarkably decrease with distance from the heating source. However, the increase of the undrained shear strength showed a dependence on the heat treatment time. The release of non-structural water with high temperatures can explain the increase in the mechanical behaviour of kaolinite